O uso argumentativo das crenças: o percurso entre a fixação da mentalidade crédula no indivíduo e a legitimação da utilização de premissas falsas e não evidenciadas em decisões jurídicas e políticas - Hellen Marinho Amorim (2020)
Brazilian society, as well as several other Western societies, is based, politically and legally, under a Democratic Rule of Law. Among the principles that govern it, one of the most solemnly obeyed by the state agents is that which imposes that yours decisions must always be reasoned. However, although this commandment has been used as an inhibitor of the decision makers’ arbitrariness, the faculty they have to use diverse and diversified argumentative premises makes room for them to depart from the (supposed) commitment they have with the truth of the facts and with evidence that shows a high degree of confidence. It is in this context that the “argumentative use of beliefs” presents as a theme to be developed. What makes belief, in its objective and evaluative senses, essentially different from other premises is, in a nutshell, the propositional falsehood and the fragility of the evidence that is used to support it. However, these characteristics are only the resultant practices of a very strong subjective inclination, linked to innumerable psychological and neurophysiological cognitive processes that form the “believer mentality” and culminate, many times, in a “believer behavior”. To that extent, the general purpose of the present study is to present a description of how this mentality and this behavior were consolidated in the human species and what are the cognitive processes related to them that modern human beings present – including to make decisions that are so concomitantly serious and indispensable. From this description, it will be possible to glimpse what happens between the mental chain of belief in the individual and their subsequent externalization in the form of an argumentative premise. To achieve these objectives, a strong consilient approach will be taken, that is, the study will be based on different areas of academic knowledge in addition to legal knowledge, focusing on Epistemology and Cognitive Sciences (evolutionary psychology, cognitive psychology, cognitive neuropsychology and cognitive neuroscience). It will be concluded that the construction of the believer mentality and behavior was naturally rooted and culturally reinforced in such a way that it is possible to affirm that any human being is a “believer subject”, that is, a bearer of a “believer mental design”. In this sense, in order to try to circumvent or lessen as much as possible the pragmatic problems arising from the argumentative use of beliefs, it will be proposed that legal and political decision makers, as well as their respective state institutions, commit themselves, in the near future, to humanistic methods of cognitive enhancement and, in a much more distant future, to cognitive bioenhancements.